MicroRNAs and type 2 diabetes - Jiali Deng; Feifan Guo (ExRNA)
Abstract MicroRNAs (miRNAs) are non-coding single strand RNAs. MiRNAs are encoded by endogenous genes with a length of about 22 nucleotides. MiRNAs play a vital role in the inhibition of post-transcriptional translation of mRNAs. In recent years, studies have discovered that miRNAs play an essensial role in the pathogenesis of type 2 diabetes. In addition, the discovery of miRNAs in the serum and plasma also provides a potential target for the discovery of disease markers. Taken together, preliminary data suggest a potential role of miRNAs in type 2 diabetes, however more clinical trials need to be studied.